Antidepressant mechanisms of ketamine: a review of actions with relevance to treatment-resistance and neuroprogression - Lullau, August P. M.; Haga, Emily M. W.; Ronold, Eivind H.; Dwyer, Gerard E. (Frontiers in Neuroscience, 2023)
Concurrent with recent insights into the neuroprogressive nature of depression, ketamine shows promise in interfering with several neuroprogressive factors, and has been suggested to reverse neuropathological patterns seen in depression. These insights come at a time of great need for novel approaches, as prevalence is rising and current treatment options remain inadequate for a large number of people. The rapidly growing literature on ketamine’s antidepressant potential has yielded multiple proposed mechanisms of action, many of which have implications for recently elucidated aspects of depressive pathology. This review aims to provide the reader with an understanding of neuroprogressive aspects of depressive pathology and how ketamine is suggested to act on it. Literature was identified through PubMed and Google Scholar, and the reference lists of retrieved articles. When reviewing the evidence of depressive pathology, a picture emerges of four elements interacting with each other to facilitate progressive worsening, namely stress, inflammation, neurotoxicity and neurodegeneration. Ketamine acts on all of these levels of pathology, with rapid and potent reductions of depressive symptoms. Converging evidence suggests that ketamine works to increase stress resilience and reverse stress-induced dysfunction, modulate systemic inflammation and neuroinflammation, attenuate neurotoxic processes and glial dysfunction, and facilitate synaptogenesis rather than neurodegeneration. Still, much remains to be revealed about ketamine’s antidepressant mechanisms of action, and research is lacking on the durability of effect. The findings discussed herein calls for more longitudinal approaches when determining efficacy and its relation to neuroprogressive factors, and could provide relevant considerations for clinical implementation.